Groundwater quality characteristics of the Anavisos Basin - Angelakopoulou, E.; Koumantakis, I.; Vasileiou, E.; Stathopoulos, N. (Bulletin of the Geological Society of Greece, 2013)
The Anavisos basin is located in the southern part of Attica and it is a part of the coastline in the Saronikos Bay. Τhe basin covers an area about 110,91 km2. The water needs for potable uses of the area are covered by EYDAP and irrigational needs by private drillings and wells. The salinization of the groundwater and the degradation of the water quality had also been observed in the past in the study area. In this research, the most recent chemical analysis showed that the salinity appears extended in the coastal zone as it was in previous decade. The salinization has proceeded into the inland, so the groundwater is characterized as saline and improper for any use in some cases. The main cause for the sea intrusion is the over-pumping exploitation of the coastline aquifers. The rational developments of the area, the lack of a sewerage system, are the main reasons for the degradation of the groundwater in the basin. Additionally there is not a wastewater treatment system in the area, for reusing these waters.